2017
DOI: 10.1007/s10545-017-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Tight metabolic control plus ACE inhibitor therapy improves GSD I nephropathy

Abstract: The onset of microalbuminuria (MA) heralds the onset of glomerulopathy in patients with glycogen storage disease (GSD) type I. Unlike tubulopathy, which responds to improved metabolic control, glomerulopathy in GSD I is considered refractory to medical intervention, and it is thought to inexorably progress to overt proteinuria and renal failure. Recent reports of reduced microalbuminuria following strict adherence to therapy counter this view. In contrast to type Ia, little is known regarding the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…recently reported amelioration of kidney disease if ACE inhibition is combined with improved metabolic control. 38 It is interesting that in these studies, improvement occurred when mean triglycerides fell to 370 [AE196] mg/dL. This is very similar to the concentration reported by Beegle et al where regression of adenomas occurred.…”
Section: Gsd Nephropathysupporting
confidence: 83%
See 1 more Smart Citation
“…recently reported amelioration of kidney disease if ACE inhibition is combined with improved metabolic control. 38 It is interesting that in these studies, improvement occurred when mean triglycerides fell to 370 [AE196] mg/dL. This is very similar to the concentration reported by Beegle et al where regression of adenomas occurred.…”
Section: Gsd Nephropathysupporting
confidence: 83%
“…With improved care, the prevalence of GSD nephropathy has dramatically fallen, and now only the minority of adults develop microalbuminuria or proteinuria (Table ). Of note, Okechuku et al, have recently reported amelioration of kidney disease if ACE inhibition is combined with improved metabolic control . It is interesting that in these studies, improvement occurred when mean triglycerides fell to 370 [±196] mg/dL.…”
Section: Discussionmentioning
confidence: 98%
“…There is increasing evidence that liver and kidney complications in glycogen storage disease are almost universal in mice (Mutel et al 2011;Clar et al 2014) and humans with poor metabolic control (Rake et al, 2002). Improved metabolic control, however, has been associated with fewer liver and kidney complications in humans with GSD-Ia (Wang et al 2011;Okechuku et al, 2017;Dambska et al, 2017). Animal studies have provided clues regarding the enzyme activity required to prevent hypoglycemia and complications in GSD-Ia.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease has developed in patients with GSD-Ia who have undergone liver transplantation, but this could be related to the use of nephrotoxic immunosuppression (Davis and Weinstein 2008;Reddy et al 2009). In contrast, recent investigations have demonstrated that kidney disease can be prevented or reversed with good metabolic control (Okechuku et al 2017;Dambska et al, 2017). The improved metabolic control in the dogs may explain the lack of renal complications, but humans will need to be followed extremely closely after any gene therapy trial using AAV to ensure that kidney disease does not develop.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen storage disease type I (GSDI) is a metabolic disease most frequently described by the presence of hypoglycemia, dyslipidemia, and long-term development pathologies, including hepatic tumors and nephropathy. Nowadays, with the optimization of the metabolic control of the patients suffering from GSDI, these complications can be delayed Okechuku et al 2017) but most of adult patients currently show hepatic tumors and/or chronic kidney disease (CKD) (Calderaro et al 2013;Gjorgjieva et al 2016;Kishnani et al 2014). In this review, we summarized the potential molecular mechanisms behind the onset of cyst development in GSDI patients, as well as the possible risk of renal carcinogenesis associated to GSDI.…”
Section: Introductionmentioning
confidence: 99%